Paralomis indica Alcock & Anderson 1899 - Tiwari, Shivam; Padate, Vinay P.; Venugopalan, Vishnu K.; Cubelio, Sherine Sonia; Takeda, Masatsune (Zenodo, 2022)
Paralomis indica Alcock & Anderson, 1899 (Figs. 6–16, Tab. 1) Paralomis indica Alcock & Anderson 1899: 15.—Alcock 1899: pl. 43, fig. 2, 2a.— Alcock 1901: 234.— Ahyong 2010: 108 (list).— Hall & Thatje 2010: 522 (list in Appendix 1).— McLaughlin et al . 2010: 13 (list). Material examined. One male (IO /SS/ANO/00001; PCL 91.2 mm, CW 102.4 mm), Bay of Bengal, FORVSS stn 29283, 6.84°N, 93.05°E, 337 m depth, HSDT (CV), coll. Dr. Usha Parameswaran, 10 December 2011. One male (IO /SS/ANO/00048; PCL 82.5 mm, CW 99.6 mm), Bay of Bengal, FORVSS stn 27924, 17.05°N, 83.30°E, 550 m depth, Expo model trawl net, coll. Dr. R. Raghu Prakash, 2 September 2010. One male (IO /SS/ANO/00049; PCL 80.9 mm, CW 94.9 mm), one ovigerous female (IO /SS/ANO/00050; PCL 64.2 mm, CW 74.0 mm), Bay of Bengal, FORVSS stn 29105, 18.83°N, 85.37°E, 614–643 m depth, HSDT (CV), coll. Dr. Rajeeshkumar M.P., 30 October 2011. One male (IO /SS/ANO/00051; PCL 81.5 mm, CW 92.2 mm), one ovigerous female (IO /SS/ANO/00052; PCL 76.1 mm, CW 90.8 mm), Bay of Bengal, FORVSS stn 29116, 10.92°N, 80.36°E, 645–654 m depth, Expo model trawl net, coll. Dr. Rajeeshkumar M.P., 8 November 2011. Two males (IO /SS/ANO/00053; PCL 74.0 mm, CW 81.2 mm, PCL 73.7 mm, CW 83.4 mm), Bay of Bengal, FORVSS stn 29117, 11.91°N, 80.14°E, 528–777 m depth, Expo model trawl net, coll. Dr. Rajeeshkumar M.P., 9 November 2011. Two males (IO /SS/ANO/00054; PCL 77.3 mm, CW 83.4 mm, PCL 77.6 mm, CW 88.2 mm), Bay of Bengal, FORVSS stn 27901, 11.10°N, 80.32°E, 645 m depth, HSDT (CV), coll. Dr. R. Raghu Prakash, 26 August 2010. Two males (IO /SS/ANO/00055; PCL 54.4 mm, CW 60.7 mm, PCL 65.8 mm, CW 71.6 mm), Bay of Bengal, FORVSS stn 29103, 18.84°N, 85.39°E, 633–655 m depth, Expo model trawl net, coll. Dr. Rajeeshkumar M.P., 29 October 2011. One male (IO /SS/ANO/00057; PCL 85.9 mm, CW 95.0 mm), Arabian Sea, FORVSS stn 31810, 12.10°N, 74.32°E, 315–326 m depth, Expo model trawl net, coll. Dr. Rajool Shanis C.P., 26 August 2013. One male (IO /SS/ANO/00059; PCL 82.4 mm, CW 92.5 mm), one female (IO /SS/ANO/00056; PCL 68.7 mm, CW 70.6 mm), Arabian Sea, FORVSS stn 31801, 12.47°N, 74.15°E, 440–449 m depth, Expo model trawl net, coll. Dr. Rajool Shanis C.P., 24 August 2013. Three males (IO /SS/ANO/00058; PCL 67.0 mm, CW 73.5 mm, PCL 69.0 mm, CW 74.2 mm, PCL 78.1 mm, CW 80.8 mm), four females (IO /SS/ ANO/00060; PCL 62.3, CW 68.1 mm, PCL 67.1 mm, CW 75.1 mm, PCL 67.9 mm, CW 72.9 mm, PCL 70.1 mm, CW 70.0 mm), Arabian Sea, FORVSS stn 39801, 8.24°N, 76.49°E, 610 m depth, Expo model trawl net, coll. Aleesha K. Shaji, 29 February 2020. Four males (IO /SS/ANO/00120; PCL 79.7 mm, CW 84.9 mm, PCL 61.1 mm, CW 63.7 mm, PCL 66.1 mm, CW 70.6 mm, PCL 59.7 mm, CW 68.9 mm), one female (IO /SS/ANO/00121; PCL 62.6 mm, CW 65.1 mm) Arabian Sea, FORVSS stn 39901, 8.64°N, 76.10°E, 1065 m depth, coll. Dr. Aneesh Kumar K. V., HSDT (CV), 23 September 2020. One juvenile male, (IO /SS/ANO/00123; PCL 27.1 mm, CW 29.9 mm), Bay of Bengal, FORVSS stn 27924, 17.05°N, 83.30°E, 550 m depth, coll. Dr. R. Raghu Prakash, Expo model trawl net, 2 September 2010. Description. Carapace broad, pyriform (PCL 0.8–1.0 CW), lateral margins sinuous, subparallel in most specimens, regularly convex in few specimens; regions distinct (Figs. 6A–D, 13A, D, G, J, 14A, D, G, J, 15A, D, G, J). Surface covered with unequal-sized conical tubercles; larger conical tubercles with acuminate apex, surface pitted (Fig. 6A–D); elongated tubercles on carapace including 1 at anterior end of branchial region. Gastric region convex, moderately elevated, with 15–17 moderately large conical tubercles, and few minute interspersed tubercles. Lateral margin of hepatic region with 3 alternately large and small conical spines. Branchial anterior margin with 5–8 alternately large and small spines, lateral margin with 4–7 alternately large and small spines, posterior margin with 9–13 small spines; dorsal surface moderately to distinctly inflated, elevation much more prominent than other regions (moderately prominent in few specimens), covered with unequal-sized conical tubercles and randomly scattered minute tubercles. Cardiac region subtriangular, moderately to distinctly depressed, with 2 submedian pairs followed by 1 median short conical tubercle. Intestinal region with 1 median and 1 pair of submedian short conical tubercles. Pterygostomian region sparsely granular, with prominent anterior spine (Fig. 7A, B). Rostrum trispinous, 0.1–0.2 PCL; broadest basally; median spine elongate conical, gently curved upwards, smooth, ventral lobe triangular, covered with granules; dorsal spines subparallel to diverging, shorter than median spine, directed obliquely upwards, tips acuminate (Fig. 7C, D). Posterior orbital margin concave, armed with short spine at inner base of outer orbital spine; outer orbital spine slender, directed anteriorly, short of or overreaching apex of cornea. Anterolateral spine slightly shorter than outer orbital spine; distance between the outer bases of anterolateral spines 0.3–0.4 CW. Ocular peduncle longer than cornea, with randomly scattered spinules, 1 large median conical spinule flanked by 3 spinules laterally and 1 or 2 spinules mesially above cornea (Fig. 7E, F). Antennular peduncle unarmed, reaching anteriorly beyond apex of antennal peduncle by length of distal antennular peduncle article (Fig. 8A, E, H). Basal antennal article with sparsely granular dorsal surface, with large distolateral spine and 1 lateral spinule. Article 2 with sparsely granular dorsal surface, angular outer margin terminating in a sharp spine, with 2 basal spinules; distolateral spine overreaching distal margin of article 4; inner margin terminating in a sharp spine, with 1 subdistal spine; distomesial spine shorter than distolateral, with one blunt basal spine. Article 3 with sparsely scattered setae (Fig. 8A, E, H). Scaphocerite a long slender spine not reaching apex of distal peduncular article, most specimens bearing 2 inner and 2 outer spines and 1 inner or 1 outer spinule, dorsal surface with 2 blunt spinules, few others bearing 3 inner and 3 outer spines and 1 blunt spinule (Fig. 8B–C, F, I). Article 4 very sparsely setose, less than half length of article 5. Maxilliped 3 pediform, widely separated basally (Fig. 8D, G, J). Ischium with crista dentata consisting of 16 teeth; accessory tooth present. Merus, carpus with single row of setae on mesial margin. Propodus triangular in cross-section, with thick bunches of grooming setae on mesial margin, outer base of triangle with row of setae. Dactylus flattened with thick bunches of grooming setae along mesial margin. Abdominal somite 2 covered with conical tubercles smaller than those on carapace (Fig. 9A, C, G, J). Somites 3–6 arranged almost in a straight line in males (Figs. 13B, E, H, K, 14B, E, H, K), curved towards right in females (Fig. 15B, E, H, K), covered with conical tubercles progressively smaller in size, margins spinose, bearing acute spines in most specimens, blunt spines in few others; marginal plates narrow to wide, indistinctly to distinctly subdivided. In males, somite 6 1.0–1.2 times longer than wide (0.9 in the juvenile male), marginal plates slightly short of or overreaching distal margin of median plate; in females, 1.0–1.4 times longer than wide. Telson bluntly triangular, slightly wider than long, with 1 submedian pair of short conical tubercles (Figs. 13B, E, H, K, 14B, E, H, K, 15B, E, H, K). Pereopods 1 (chelipeds) unequal, spination similar in both sexes. Major cheliped of males moderately to distinctly inflated (Fig. 10A–C), ratio of height of major cheliped and minor cheliped 1.6–2.3 in males, 1.0– 1.9 in females; minor cheliped slender (Fig. 10D–F). Coxae smooth to sparsely granular in males, distal margins minutely tuberculate (Fig. 9B, D, F, H); in females, coxae smooth, covered with long silky setae (Fig. 8B). Ischiobasis sparsely covered with conical spines, longer and numerous in smaller specimens. Merus sparsely covered with conical spines on mesial and lateral surfaces, distal margin of lateral surfaces with 4 short spines; dorsal margins of larger chelipeds in both sexes with 4 strong spines, those of smaller chelipeds with 4 comparatively smaller spines. Carpus dorsal margins with 4 large and 1 small spines, ventral margin with randomly scattered spinules, mesial surface with sparsely placed spinules (longest in smaller specimens), lateral surfaces with 3 irregular rows of well-spaced shorter spines. Propodus with 1 pair of subdistal spines followed by 1 irregular row of spines on dorsal margin, ventral margin with 1 irregular row of small well-spaced spines, mesial surfaces with 2 rows of well-spaced spinules on lower portion, upper portion with irregular patch of spinules, lateral surfaces with 4 rows of well-spaced small spines and 1 or 2 rows of spinules; mesial and lateral surfaces with spines bearing setal tufts anteriorly, extending onto proximal portion of pollex. Major cheliped 1.0–1.5 PCL in males, 1.0– 1.1 in females; upper palm length 0.9–1.2 times height in males (2.0 in juvenile male), 0.9–1.3 in females; upper palm length 1.3–1.7 times width in males, 1.3–1.5 in females; occlusal margins of fingers corneous for distal one-fourth, proximally with 4 low calcareous nodules, proximal nodule largest; dactylus dorsal margin broadly convex, with rows of tufts of golden setae and 1 large proximal spine (Fig. 10A–C), 1.1–1.3 times longer than dorsal margin of palm in males (0.6 in juvenile male), 1.2–1.7 in females. Minor cheliped 0.9–1.3 PCL in males, 0.9–1.1 in females; upper palm length 0.9–1.2 times height in males (1.2 in juvenile male), 1.0– 1.2 in females; occlusal margin corneous in distal half, proximally crenulate; dactylus dorsal margin broadly convex, with rows of tufts of golden setae and 2–3 small proximal spines (Fig. 10D–F), 1.8–2.1 times longer than dorsal margin of palm in males (1.7 in juvenile male), 1.6–1.9 in females. Pereopods 2–4 similar, elongate, spinose (Fig. 11A–C, E–G, I–K). Coxae smooth, very sparsely spinulose, covered with long silky setae, margins bearing tufts of setae. Ischiobases with dorsal surface smooth, sparsely setose, ventral surfaces with proximally setose patch, distal two-thirds with 8–12 randomly scattered short conical tubercles (spines in smaller specimens) bearing a ring of setae around the apex (largest on P4), proximal and distal margins with a row of spinules, anterior and posterior margins with small random tufts of setae. Meri compressed, shorter than carapace in both sexes; extensor margins with 2–6 spinules and 4–6 spines (fewest in smaller specimens), distal margins with 3–4 spines; dorsal surfaces with an irregular row of 3–8 (fewest in smaller specimens) spines and randomly scattered spinules; flexor margins with 2 irregular rows of 4–7 spines (fewest in smaller specimens), ventral surfaces sparsely spinulose; merus of pereopod 3 slightly longer than that of pereopod 2 and pereopod 4. Carpi slightly shorter than to approximately two-thirds meral length, subcircular in cross-section; extensor margins with 5–6 spines; dorsal surfaces with 5–6 spines, and randomly scattered spinules in few specimens; flexor margins sparsely spinulose. Propodi dorsoventrally flattened, shorter than meri, with a distal ring of 5–7 spines; extensor margins with 5–6 spines; dorsal surfaces with 2 rows of 5–6 spines; flexor margins with 5–7 spines, distinct dense setose patch on distal half (in some specimens only on P4); ventral surfaces with 2 irregular rows of 4–7 setose spinules (fewest in smaller specimens). Dactyli broadly curved; slightly longer than extensor margins of propodi; extensor margins with tufts of setae on distal two-thirds to three-fourths, 3 apically corneous spines and a random spinule proximally; lateral proximal surfaces with short, distinct sulcus, flanked ventrally by 1 small, corneous spine; flexor margin lined with 10–12 movable spinules (Fig. 11D, H, L). Pereopod 2 length 1.5–2.5 PCL in males (1.4 in juvenile male), 1.4–1.6 in females. Merus 0.4–0.6 PCL in males (0.4 in juvenile male), 0.4 in females; length: height ratio 2.3–4.5 in males, 2.4–3.1 in females. Carpus 0.6–0.7 merus length in males (0.7 in male juvenile), 0.7 in females. Propodus 0.7–0.9 merus length in males, 0.7–0.8 in females; length: height ratio 3.6–6.6 in males, 3.5–6.1 in females. Dactylus 1.0–1.3 propodus length in males, 1.1–1.3 in females. Pereopod 3 length 1.5–2.5 PCL in males, 1.4–1.6 in females. Merus 0.4–0.7 PCL in males (0.4 in juvenile male), 0.4 in females; length: height ratio 2.6–4.0 in males, 2.5–3.1 in females. Carpus 0.6–0.7 merus length in males (0.6 in juvenile male), 0.7 in females. Propodus 0.7–0.9 merus length in both sexes (0.9 in juvenile male); length: height ratio 3.6–6.8 in males, 3.4–5.0 in females. Dactylus 1.0–1.3 propodus length in males (0.9 in juvenile male), 1.1–1.3 in females. Pereopod 4 length 1.4–2.4 PCL in males, 1.4–1.6 in females. Merus 0.4–0.6 PCL in males, 0.4 in females; length: height ratio 2.6–4.2 in males, 2.6–3.3 in females. Carpus 0.6–0.7 merus length in males (0.6 in juvenile male), 0.7 in females. Propodus 0.7–0.9 merus length in males, 0.8–0.9 in females; length: height ratio 3.5–6.0 in males, 3.4–5.0 in females. Dactylus 1.0–1.4 propodus length in males (0.9 in juvenile male), 1.2–1.3 in females. Morphological variability. The present material of P. indica collected from the southeast Arabian Sea, western Bay of Bengal and southeast Andaman waters (off Great Nicobar Island) exhibited high intraspecific variations (both intersexual and ontogenic) in the form of the carapace and dorsal rostral spines, nature of the branchial and cardiac regions, abdominal marginal spines, and pereopod length: PCL ratios for P2–P4. The present material was classified into 5 geographical regions (Arabian Sea off Trivandrum, Arabian Sea off North Kerala, southwestern Bay of Bengal, northwestern Bay of Bengal and Andaman waters) and 5 size-classes (20–30 mm PCL, 50–60 mm PCL, 60–70 mm PCL, 70–80 mm and 80–90 mm PCL) to infer the morphological and morphometric variations. In the Trivandrum region, the single male in the 50–60 mm size-class was characterized by convex carapace lateral margins, moderate branchial inflation, protruding cardiac region (in posterior view), V-shaped dorsal rostral spines, prominent abdominal marginal spines and lower PL/PCL ratio (for P2–P4) of 1.5. The 60–70 mm size-class of the males (n = 4) was characterized by convex carapace lateral margins, moderate branchial inflation, protruding cardiac region, V-shaped dorsal rostral spines, prominent abdominal marginal spines and slightly higher PL/PCL ratio of 1.5–1.8 (Fig. 13A–C); the females in this size-class (n = 4) differed in the slightly lower PL/PCL ratio of 1.4–1.6. The 70–80 mm size-class of the males (n = 2) was characterized by broadly convex carapace lateral margins, distinct branchial inflation, sunken cardiac region, V-shaped to curved dorsal rostral spines, prominent abdominal marginal spines and PL/PCL ratio of 1.4–2.1 (Fig. 13D–F); the single female in this size-class differed in having convex carapace lateral margins, moderate branchial inflation, protruding cardiac region and PL/PCL ratio of 1.5 (Fig. 15A–C). Off North Kerala, the single female in the 60–70 mm size-class was characterized by sinuous carapace lateral margins, distinct branchial inflation, sunken cardiac region, curved dorsal rostral spines, prominent abdominal marginal spines and PL / PCL ratio of 1.4 (Fig. 15D–F). The 80–90 mm size-class (2 males) was characterized by convex carapace lateral margins, moderate to distinct branchial inflation, protruding to sunken cardiac region, Vshaped to curved dorsal rostral spines, prominent to short abdominal marginal spines and PL / PCL ratio of 1.9–2.1 (Fig. 13H–J). In the southwestern Bay of Bengal, the 70–80 mm size-class of the males (n = 4) was characterized by variations in carapace lateral margins (broadly convex to sinuous), branchial inflation (moderate to distinct), nature of cardiac region (protruding to sunken), curved dorsal rostral spines, abdominal marginal spines (prominent to short) and PL/PCL ratio of 1.7–2.3 (Figs. 13J–L, 14A–C); the single female in the above size-class possessed sinuous carapace lateral margins, distinct branchial inflation, protruding cardiac region, curved dorsal rostral spines, prominent abdominal marginal spines and PL/PCL ratio of 1.4–1.5 (Fig. 15G–I). The single male in the 80–90 size class was characterized by broadly convex carapace lateral margins, moderate branchial inflation, protruding cardiac region, curved dorsal rostral spines, short abdominal marginal spines and PL/PCL ratio of 2.0–2.1. In the northwestern Bay of Bengal, the single juvenile male in the 20–30 mm size-class was characterized by sinuous carapace lateral margins, moderate branchial inflation, protruding cardiac region, V-shaped dorsal rostral spines, short abdominal marginal spines and PL / PCL ratio of 1.4–1.5 (Fig. 14J–L). The single male in the 50–60 mm size-class was characterized by sinuous carapace lateral margins, moderate branchial inflation, protruding cardiac region, V-shaped dorsal rostral spines, short abdominal marginal spines and PL / PCL ratio of 1.7 (Fig. 14G–I). The single male in the 60–70 mm size-class was characterized by broadly convex carapace lateral margins, distinct branchial inflation, sunken cardiac region, V-shaped dorsal rostral spines, (abdomen missing) and PL / PCL ratio of 1.9; the single female in the above size-class differed from the male in having sinuous carapace lateral margins, curved dorsal rostral spines, prominent abdominal marginal spines and PL / PCL ratio of 1.4–1.5 (Fig. 15J–L). The 80–90 mm size class (2 males) was characterized by sinuous carapace lateral margins, distinct branchial inflation, sunken cardiac region, curved dorsal rostral spines, short abdominal marginal spines and PL / PCL ratio of 2.0–2.3 (Fig. 14D–F). In the Andaman waters, the single male in the 80–90 mm size-class was characterized by sinuous carapace lateral margins, distinct branchial inflation, sunken cardiac region, curved dorsal rostral spines, short abdominal marginal spines and PL/PCL ratio of 2.4–2.5. In conclusion: a. The largest males (80–90 mm) were generally characterized by curved dorsal rostral spines, short abdominal marginal spines and PL/PCL ratio> 1.9. b. High variability in the morphological characters among the males in the 50–60 mm size-class, as well as both the sexes in the 60–70 mm and 70–80 mm size-classes. c. All females were characterized by a lower PL/PCL ratio compared to the males in their corresponding sizeclasses. Genetic data. : Published as part of Tiwari, Shivam, Padate, Vinay P., Venugopalan, Vishnu K., Cubelio, Sherine Sonia & Takeda, Masatsune, 2022, Paralomis White, 1856 (Crustacea: Decapoda: Anomura) from India, with morphological variability in Paralomis indica Alcock & Anderson, 1899, pp. 301-329 in Zootaxa 5091 (2) on pages 310-325, DOI: 10.11646/zootaxa.5091.2.4, http://zenodo.org/record/5843678 : {"references": ["Alcock, A. & Anderson, A. R. S. (1899) Natural history notes from H. M. Royal Indian Marine Survey Ship \" Investigator, \" Commander T. H. Heming, R. N., commanding. - Series III, no. 2. An account of the deep-sea Crustacea dredged during the surveying-season of 1897 - 98. Annals and Magazine of Natural History, Series 7, 3, 1 - 27. https: // doi. org / 10.1080 / 00222939908678071", "Alcock, A. (1901) A descriptive catalogue of the Indian deep-sea Crustacea Decapoda Macrura and Anomala, in the Indian Museum. Being a revised account of the deep-sea species collected by the Royal Indian Marine Survey Ship Investigator. Trustees of the Indian Museum, Calcutta, iv + 286 pp., pls. 1 - 3. https: // doi. org / 10.5962 / bhl. title. 30840", "Ahyong, S. T. (2010) The marine fauna of New Zealand: king crabs of New Zealand, Australia and the Ross Sea (Crustacea: Decapoda: Lithodidae). NIWA Biodiversity Memoir, 123, 1 - 194.", "Hall, S. & Thatje, S. (2010) King crabs up-close: ontogenetic changes in ornamentation in the family Lithodidae (Crustacea, Decapoda, Anomura), with a focus on the genus Paralomis. Zoosystema, 32 (3), 495 - 524. https: // doi. org / 10.5252 / z 2010 n 3 a 10", "McLaughlin, P. A., Komai, T., Lemaitre, R. & Rahayu, D. L. (2010) Annotated checklist of anomuran decapod crustaceans of the world (exclusive of the Kiwaoidea and families Chirostylidae and Galatheidae of the Galatheoidea) Part I - Lithodoidea, Lomisoidea and Paguroidea. The Raffles Bulletin of Zoology, Supplement, 23, 5 - 107.", "Takeda, M. & Bussarawit, S. (2007) A new species of the genus Paralomis White, 1856 (Crustacea, Decapoda, Anomura, Lithodidae) from the Andaman Sea. Bulletin of the National Museum of Nature and Science, Series A (Zoology), 33 (2), 51 - 59."]}